A-State-Of-The-Art review on modular building connections. (December 2021) - Rajanayagam, Heshachanaa; Poologanathan, Keerthan; Gatheeshgar, Perampalam; Varelis, George E.; Sherlock, Paul; Nagaratnam, Brabha; Hackney, Phil
Abstract: Modular Building System (MBS) is an emerging offsite construction technique, which uses prefabricated units, transported, and assembled onsite. In MBS construction process, designing stage is considered as the most significant stage. One of the critical concerns in designing MBSs is to maintain and to ensure the structural integrity of the assembly against critical loading conditions. Connections in the MBSs as a crucial part of the off-site construction, plays a prominent role in providing the essential performance and integrity for the assembled MBS. Hence, it is indispensable to analyse the existing connections used in industry and to investigate the benefits and limitations of their application in MBS construction. A thorough study on connection types will evaluate their capabilities in addressing functional requirements and will exhibit their potential to serve as a benchmark for a range of future modular construction techniques. Thus, this paper presents a review on various forms of inter-modular connection systems used in the contemporary construction industry. It covers the role of connections in the automation of assembly and disassembly of modular units; architectural, structural, and constructional challenges faced by the industry in using them; and their performance under different loading conditions. In addition, numerical studies performed on a selected intermodular connection model is also presented, investigating, and validating the mechanical behaviour of connection and justifying the applicability of such models in predicting connection behaviour. Finally, based on the review, suggestions to address modern construction obstacles by adding new information to the literature and then to overcome challenges in the wide adoption of the MBS in construction industry are presented. The outcome of this study assists in overcoming obstacles and encourages potential growth of MBS and/or off-site construction techniques in building construction industry.